Efeito do treinamento físico aeróbico na prevenção das enxaquecas e implicações do sistema endocanabinoide: um estudo clínico randomizado e controlado - Oliveira, Arão Belitardo de [UNIFESP] (2016)
Objective: To test the efficacy of aerobic exercise training performed at the intensity corresponding to the ventilatory threshold on migraine prevention and mood improvement, and explore correlational hypothesis with plasma anandamide concentrations. Methods: The study included participants from both sex, aged 20 to 60 years, physically inactive, with episodic migraine with/without aura (ICHD-II) under no prophylaxis treatment, as well as healthy subjects. Participants were randomly assigned to receive intervention with aerobic exercise training (trained groups) on treadmill for 12-weeks, 3 sessions/week, 30 minutes per session, or waitlist (sedentary groups). Days with pain and migraine frequency were the primary outcome variables. The number of abortive medication used, plasma anandamide concentration, and aerobic fitness were chosen as secondary outcome variables, and mood scores were chosen as tertiary outcome variables. Participants underwent maximal cardiopulmonary exercise test, blood sampling, and psychometric interviews before and after the intervention period. All participants gave signed informed consent. Migraine patients were always assessed in the interictal period. Results: Fifty participants (mean±SD age = 36.2±10.9 years and BMI = 26.5±4.5 kg/m2) were analysed. They were allocated to the following groups: healthy sedentary (n = 13), healthy trained (n = 12), migraine sedentary (n = 12), and migraine trained (n = 13). At baseline, there were no significant differences in anthropometric characteristics, plasma anandamide concentration, and aerobic fitness between groups, neither in clinical variables between migraine groups. Migraine groups showed higher scores for negative mood domains compared to healthy sedentary group. After intervention period, there was a significant reduction in both primary outcome variables in migraine trained group, without significant changes in these variables in migraine control group. Plasma anandamide concentrations was significantly reduced in healthy sedentary group and showed a marginally significant reduction in migraine trained group. Thel negative mood domains anxiety, depression, and fatigue were significantly reduced only in migraine trained group, without changes in any domain for the other groups. There was a strong inverse correlation between reduction in medication consumption and increase in aerobic fitness, as well as a positive correlation between the reduction in medication consumption and plasma anandamide concentration, but only for migraine trained group. In the whole cohort, plasma anandamide concentration was positively correlated with all negative mood domains scores. Conclusion: Aerobic exercise training performed at the intensity corresponding to the ventilatory threshold is effective for migraine prevention and mood improvement. These therapeutic effects may be related to reduction in plasma anandamide concentration.